2009
DOI: 10.1089/sur.2008.078
|View full text |Cite
|
Sign up to set email alerts
|

Does Preoperative Core Needle Biopsy Increase Surgical Site Infections in Breast Cancer Surgery? Randomized Study of Antibiotic Prophylaxis

Abstract: Core needle biopsy did not increase the incidence of SSI. Antibiotic prophylaxis did not prevent SSI, probably because so few infections occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The procedure from which CNBs can be obtained allows for a more limited contamination of specimens even if the tissue levels are lower than those of SEBs. Indeed, even though breast tissues drawn from SEBs were obtained under fully aseptic conditions, surgical excision involves an unavoidable exposure to the external environment 34 , 35 . However, in the present study, the collection of environmental controls showed that such external contamination was undetectable.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure from which CNBs can be obtained allows for a more limited contamination of specimens even if the tissue levels are lower than those of SEBs. Indeed, even though breast tissues drawn from SEBs were obtained under fully aseptic conditions, surgical excision involves an unavoidable exposure to the external environment 34 , 35 . However, in the present study, the collection of environmental controls showed that such external contamination was undetectable.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a 5% absolute difference in SSI rates between patients who received a single preoperative dose of antibiotic and those who did not, a minimum of 400 cases and 400 controls were necessary to attain 80% statistical power. This was based on an expected difference of SSI rates from 8% for the patients who did not receive any antibiotics to 3% for those who received a single dose of preoperative antibiotic [ 6 , 7 , 9 – 11 , 14 16 ]. In the bivariable analysis, a Z -/ t -test was used for normally distributed data, Wilcoxon Rank-Sum test for skewed data, and Fisher's Exact or Chi-square test for categorical data.…”
Section: Discussionmentioning
confidence: 99%
“…1. Nine randomized controlled trials (23–31) encompassing 3,720 patients undergoing breast surgery were retrieved from the electronic databases for systematic review. To generate a summated outcome, we divided patients into two groups: an antibiotics group and non‐antibiotics group (patients received either no antibiotics or a placebo).…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative prophylactic antibiotics are recommended in many surgical disciplines to reduce the SSI‐related morbidity and cost (18); however, recent published studies on various clean surgical procedures have not favored the routine use of antibiotics prophylactically (19–22). Randomized controlled trials (23–31) and previously published reviews in 2006 (32,33) reported equivocal results on the effectiveness of prophylactic antibiotics in the reduction of breast SSI. The objective of this article is to re‐visit and re‐evaluate the role of preoperative prophylactic antibiotics in patients undergoing breast surgery in terms of reduction in SSI rate.…”
mentioning
confidence: 99%